PERANCANGAN E-MARKETPLACE UMKM DI KABUPATEN KARO - Br. Tarigan, Kris Inanta; Hutapea, Marlyna I.; Nainggolan, Rena (Universitas Methodist Indonesia, 2023)
Small and medium-sized enterprises or better known as SMEs. SMEs are developing very rapidly and have an important role for the economy. The main obstacle faced by SMEs actors is the difficulty of promoting products widely and this occurs in almost all SMEs, including Karo Regency SMEs, in terms of overcoming this, various strategies have been implemented by the Karo Regency Cooperative and SMEs services including: holding exhibitions in various regions, collaborating with third parties and provide business consulting services. However, these strategies are considered less effective because there are still many weaknesses such as the large costs required, limited SMEs that can participate, short time, and small scope of promotion. The purpose of this study is to develop aweb-based e-Marketplace system as a medium for promoting SMEs products widely and to increase income for SMEs players in Karo Regency.